2021
DOI: 10.1002/leg3.86
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of common bean (Phaseolus vulgaris L.) germplasm for morphological and seed nutrient traits from Western Himalayas

Abstract: Common bean (Phaseolus vulgaris L.) is considered as one of the principle grain legume crops grown in Western Himalayas of Jammu and Kashmir, India. This region holds great diversity of common bean germplasm. The purpose of present study was to characterize 109 common bean genotypes collected from different hotspots for morphological traits-plant growth (growth habit, growth type, and twinning habit); leaf (color, size, and shape); flower (color, stripping on outer petal); pod (shape in relation to suture, sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Dry edible beans supply a major source of quality protein (23%), which is high in lysine and thus complements most cereals. In addition, beans are low in fat content and are packed with complex carbohydrates (55-65%), fiber, vitamins, and minerals ( Mitchell et al, 2009 ; Petry et al, 2015 ; VazPatto et al, 2015 ; Vidigal Filho et al, 2020 ; Jan S. et al, 2021 ; Choudhary et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dry edible beans supply a major source of quality protein (23%), which is high in lysine and thus complements most cereals. In addition, beans are low in fat content and are packed with complex carbohydrates (55-65%), fiber, vitamins, and minerals ( Mitchell et al, 2009 ; Petry et al, 2015 ; VazPatto et al, 2015 ; Vidigal Filho et al, 2020 ; Jan S. et al, 2021 ; Choudhary et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seed yield also had a very broad range with genotypes WBP3, WBP4, WBP6, WBP12 and WBC1 being the highest yielder. In Kashmir valley, substantial diversity in beans has been reported by various earlier workers (Iram Saba et al, 2016, Sofi et al, 2020and Jan et al, 2021 for yield and quality traits, even though the spectrum of diversity may be comparatively lesser as the pinto and cranberry beans form a small subset of landrace diversity of beans in Western Himalayan Kashmir valley that comprises huge diversity in small seeded red beans, kidney beans as well as other market classes. Elsewhere, significant diversity in pinto and cranberry beans has been reported in Turkey (Balkaya and Ergun, 2008), Pakistan (Nawaz and Farhatullah, 2020), and Africa (Mukankusi et al, 2019).…”
Section: Resultsmentioning
confidence: 90%
“…The western Himalayan region is a rich repository of bean genetic resources evolved over generations of farmer selection and substantial variability in Western Himalayan bean landraces has been reported in earlier studies across different qualitative traits (Rani Shama et al, 2019, Sofi et al, 2020, Jan et al, 2021. Despite the fact that most of the accessions had similar seed characteristics as well as plant growth habits on account of similar ecology viz., intercropping, there was substantial variability for various qualitative traits such as pod shape and curvature, quantitative traits including those related to phenology and yield.…”
Section: Resultsmentioning
confidence: 96%
“…Earlier reports also suggested that seed mineral content showed huge variation in common bean germplasm. Seed mineral concentrations such as Mg, Ca, Fe, Zn, and Cu of 60 common bean genotypes collected from the Western Himalayas varied from 1,220.5 to 2,737.5 ppm, 300–5,350 ppm, 80.5–180.6 ppm for Fe, 14.64–104.08 ppm, and .9–13.4 ppm, respectively ( Jan et al, 2021 ). The average seed Ca concentration was recorded as 1.37 and 1.41 g kg −1 , whereas, the average Fe seed content was recorded as 79.57 and 85.95 mg kg −1 from common bean seeds obtained through pedigree and single seed descent methods respectively ( Ribeiro et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%